Factors that affect satisfaction Generation Z Jkn Mobile Application Users At the Central City Health Center of Gorontalo City - Ramla Akase; Herlina Jusuf; Ayu Rofia Nurfadillah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The Mobile JKN application as a digital health service innovation still faces various obstacles, such as feature limitations, accounts that often exit automatically, and application function limitations. This problem shows that the quality of the system, information quality, and service quality are not optimal which has the potential to reduce user satisfaction, especially Generation Z. This study aims to analyze the factors that affect the satisfaction of Mobile JKN application users Generation Z at the Central City Health Center, Gorontalo City. Types of quantitative research, analytical survey research methods with a cross sectional approach. The population in this study is all generation Z participants at the health facility of the Kota Tengah Health Center of Gorontalo City who use Mobile JKN and actively visit in 2025 amounting to 152 people, the total sample is 111 respondents, with accidental sampling techniques. Data analysis was conducted using a Simple Linear Regression test. The results of the study showed that the quality of the system (p=0.047), the quality of information (p=0.004), and the quality of service (p=0.011) had a significant influence on the satisfaction of users of the JKN Mobile Application. The results of the determination coefficient showed that the quality of the system had an effect of 3.6%, information quality of 7.3%, and service quality of 5.8% on user satisfaction. In conclusion, system quality, information quality, and service quality have a positive influence on user satisfaction in Generation Z at the Kota Tengah Health Center, Gorontalo City. BPJS Kesehatan is recommended to improve application stability, clarity of information, and service response. The Gorontalo City Central City Health Center is recommended to increase the assistance of Mobile JKN application users.